Предмет: Математика, автор: fddfssdffsd15

Помогите решить пожалуйста.

Приложения:

Ответы

Автор ответа: wturm
0

f(x) = 7 {x}^{3} - 2 {x}^{2} + 1  \\  f(0) = 7 \times 0 - 2 \times 0 + 1 = 1 \\ f(3) = 7 \times  {3}^{3}  - 2 \times  {3}^{2}  + 1 = 7 \times 27 - 2 \times 9 + 1 = 172 \\ f( - 2) = 7 \times ( { - 2})^{3}  - 2 \times ( { - 2})^{2}  + 1 =  - 63 \\ f( \frac{1}{2}) = 7 \times (  { \frac{1}{2}) }^{3}  - 2 \times ( { \frac{1}{2}) }^{2}  + 1 =  \frac{7}{8}  -  \frac{1}{2}  + 1 =  \frac{3}{8}  + 1 = 1 \frac{3}{8}
Похожие вопросы
Предмет: Математика, автор: nicat201021
Предмет: Информатика, автор: lita552